CESifo World Economic Survey August 2012 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Benjamin Born (CESifo World Economic Survey, 2012)
World Economic Climate: World economic climate suffers setback - Economic Expectations: Economic expectations less positive - Inflation: Lower price expectations - Currencies: Yen and British pound seen as overvalued - Interest Rates: Decline in short-term interest rates expected - Special Topic: Growing protectionism endangers cross-border investment
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies